Perlmutter ailesi - Istrati, Panait., 1884-1935.; Yiğitler, Nuriye (Istanbul : Oda, 1991)
A Roman Jewishes's drama and humanity's problems.
This book is in Turkish.
Keywords: Jewishes's drama -- Fiction